Guidelines on the use of extracorporeal photopheresis. (January 2014) - Knobler, R.; Berlin, G.; Calzavara‐Pinton, P.; Greinix, H.; Jaksch, P.; Laroche, L.; Ludvigsson, J.; Quaglino, P.; Reinisch, W.; Scarisbrick, J.; Schwarz, T.; Wolf, P.; et al.
Abstract: Background: After the first investigational study on the use of extracorporeal photopheresis for the treatment of cutaneous T‐cell lymphoma was published in 1983 with its subsequent recognition by the FDA for its refractory forms, the technology has shown significant promise in the treatment of other severe and refractory conditions in a multi‐disciplinary setting. Among the major studied conditions are graft versus host disease after allogeneic bone marrow transplantation, systemic sclerosis, solid organ transplant rejection and inflammatory bowel disease. Materials and methods: In order to provide recognized expert practical guidelines for the use of this technology for all indications the European Dermatology Forum (EDF) proceeded to address these questions in the hands of the recognized experts within and outside the field of dermatology. This was done using the recognized and approved guidelines of EDF for this task. Results and conclusion: These guidelines provide at present the most comprehensive available expert recommendations for the use of extracorporeal photopheresis based on the available published literature and expert consensus opinion.